Determinants of Obesity in the Hispanic Preschool Population: An Integrative Review. Issue 3 (29th June 2015) - Innella, Nancy; Breitenstein, Susan; Hamilton, Rebekah; Reed, Monique; McNaughton, Diane B.
Abstract: Objective(s): The purpose of this integrative review was to identify factors associated with obesity in Hispanic preschool children. Design and Sample: Integrative research review based on strategies described by Whittemore and Knafl. Thirty‐five research reports using qualitative and/or quantitative methods and including a majority of participants (parents or preschool‐aged children) of Hispanic ethnicity. Measures: Data were analyzed using the Matrix Method. Results: Decreased physical activity of the child and increased maternal body mass index were found as contributors to obesity in the preschool, Hispanic population. The relationship between maternal feeding practices and beliefs, food choices and childhood obesity are widely studied with little consistency in findings across studies. Conclusions: Public health nurses can work with communities to promote physical activity and safe outdoor places for exercise. In addition, they can advocate for the availability of healthy food choices in neighborhood schools. Maternal feeding practices, acculturation, and the child's environment require further research.